Reader Response: Stroke Among SARS-CoV-2 Vaccine Recipients in Mexico: A Nationwide Descriptive Study. (11th October 2022) - Stoiloudis, Panagiotis; Parissis, Dimitrios; Afrantou, Theodora; Grigoriadis, Nikolaos; Ioannidis, Panagiotis
Abstract : We read with great interest the article by Lopez-Mena et al. 1 We present our experience with a 28-year-old man who was admitted to our hospital with right-sided weakness on awakening. The patient was febrile for 2 days after the second dose of the BNT162b2 vaccination against SARS-CoV-2. His medical history was unremarkable. Brain magnetic resonance imaging revealed an acute ischemic stroke in the distribution of the left posterior cerebral artery.